One new species of free-living marine nematode from the Yellow Sea, China - Hao, Yingdong; Hu, Quanan; Huang, Yong (Zootaxa, 2021)
A new species of Setostephanolaimus Tchesunov, 1994, S. longiseta sp. nov. was discovered in an intertidal sand beach along the Rizhao coast of the Yellow Sea. It is characterized by its long and slender body, long cephalic setae (longer than 20 µm and 16 µm in males and females, respectively) and subcephalic setae, long spicules (longer than 90 µm), gubernaculum with dorsal hooked apophyses, along with presence of 10–12 tubular precloacal supplements in males. Updated dichotomous key for species of the genus Setostephanolaimus is also given.